Fast Iterative Division of p-adic Numbers - KRISHNAMURTHY, E. V; MURTHY, V. K (IEEE transactions on computers, 1983)
A fast iterative scheme based on the Newton method is described for finding the reciprocal of a finite segment p-adic numbers (Hensel code). The rate of generation of the reciprocal digits per step can be made quadratic or higher order by a proper choice of the starting value and the iterating function. The extension of this method to find the inverse transform of the Hensel code of a rational polynomial over a finite field is also indicated.